The Link between Social Wellbeing, Belonging, and Connectedness of International Students in Australian High Schools - Hurem, Aida; Rowan, Leonie; Grootenboer, Peter (Frontiers in Education, 2021)
The number of international students enrolled in Australian high schools has increased dramatically over the last decade. However, limited research has investigated the unique needs and experiences of these students. In response to a general lack of knowledge relating to this population, a sample of 225 international high school students (93 males, 129 females, 3 other) enrolled in Year 10-12 in Australian independent schools were surveyed to investigate their social wellbeing. The survey included measures of social wellbeing, online and face-to-face connectedness, sense of belonging to their home country as well as in Australia, and the strength of their school connectedness, with the aim of identifying the most significant factors that predicted social wellbeing. Although all factors made some contribution to social wellbeing, the strongest predictors were a sense of Australian belonging and school connectedness. We also investigated students’ perceptions around connectedness to their social community and face-to-face and online environments, and whether there were any links between online connectedness, social wellbeing and belonging. While no statistically significant relationships were revealed for online and face-to-face connectedness and their impact upon students’ social wellbeing and sense of belonging, the findings revealed the nature of positive and online experiences, and that while risks of online activities were substantial, in general, participating in online activity brought more benefits than harm. Additionally, an unexpected finding revealed that over time, the international students’ sense of belonging and social wellbeing steadily decreased, which indicates an increased need for support for these students as they progress through the student life in Australia.